PptAB Exports Rgg Quorum-Sensing Peptides in Streptococcus - Chang, Jennifer C. (PLoS One, 2016)
A transposon mutagenesis screen designed to identify mutants that were defective in peptide-pheromone signaling of the Rgg2/Rgg3 pathway in Streptococcus pyogenes generated insertions in sixteen loci displaying diminished reporter activity. Fourteen unique transposon insertions were mapped to pptAB, an ABC-type transporter recently described to export sex pheromones of Enterococcus faecalis. Consistent with an idea that PptAB exports signaling peptides, the pheromones known as SHPs (short hydrophobic peptides) were no longer detected in cell-free culture supernatants in a generated deletion mutant of pptAB. PptAB exporters are conserved among the Firmicutes, but their function and substrates remain unclear. Therefore, we tested a pptAB mutant generated in Streptococcus mutans and found that while secretion of heterologously expressed SHP peptides required PptAB, secretion of the S. mutans endogenous pheromone XIP (sigX inducing peptide) was only partially disrupted, indicating that a secondary secretion pathway for XIP exists.